The Values of Islamic Education Based on Sufism in the Manaqib Tradition - Saepudin Saepudin; Rohimin Rohimin; Suhirman Suhirman; Meri Lestari (Journal Evaluation in Education (JEE), 2025)
Purpose of the Study: 1) describe how the manaqiban tradition influences the development of Islamic Education through Sufi values; (2) explore the impact of Sufi culture in the manaqiban tradition on the surrounding community; (3) analyze the Sufi values that support the development of Islamic Religious Education; and (4) examine how Sufi values manifest in students' daily lives. Methodology: This qualitative research uses an exploratory approach, with data collected through documentation, observation, and interviews, followed by descriptive analysis. Main Findings: First, the regular practice of the manaqiban tradition positively influences Islamic Education; second, the Sufi culture embedded in the tradition helps prevent radicalism, encourages social solidarity, and promotes tolerance within the community; third, the implementation of Sufi values in Islamic Education development occurs through studying Sufi texts, mentoring by ustadz and administrators, and engaging in religious; and fourth, the Sufi values adopted by students include repentance (taubat), fear (khauf), hope (raja`), asceticism (zuhud), poverty (fakir), patience (sabar), and contentment (ridha). Novelty/Originality of this study: Its focus is on the influence of traditional Sufi practices, like the manaqiban, on the contemporary development of Islamic education, providing insights into how these values can contribute to addressing modern issues such as radicalism and materialism. This study contributes to the broader understanding of how traditional religious practices and values can be integrated into modern educational contexts, emphasizing the need for a more holistic approach to Islamic education that fosters both spiritual and moral development in the face of globalization.